God’s Spirit, the human spirit, and the outpouring of the spirit - Welker, Michael (Leaning into the Spirit, 2019)
For centuries, understanding the doctrine of God’s Spirit was overshadowed, if not blurred by a metaphysical understanding of the spirit. This understanding goes back to Aristotle and the Stoics. Aristotle’s Metaphysics (Book 12) offers a fascinating identification of spirit and reason. It centered all thinking about the spirit on reflexive and self-reflexive knowledge. An intellectual understanding of the spirit in bipolar relations (subject and object, mind and reality, thought and the material) characterized the orientation. In the following, I should like to show that the biblical orientation on God’s Spirit and the figure of the “outpouring of the Spirit,” a figure often considered strange, offer a much richer understanding, not only of God and God’s workings but also of human nature and our cognitive and ethical capacities. Above all, the biblical understanding enables us to see how the Divine Spirit establishes a differentiated Body of Christ with many fruits and gifts for the common good and for the glory of God.